2013
DOI: 10.1155/2013/276478
|View full text |Cite
|
Sign up to set email alerts
|

-Norm Regularization in Volumetric Imaging of Cardiac Current Sources

Abstract: Advances in computer vision have substantially improved our ability to analyze the structure and mechanics of the heart. In comparison, our ability to observe and analyze cardiac electrical activities is much limited. The progress to computationally reconstruct cardiac current sources from noninvasive voltage data sensed on the body surface has been hindered by the ill-posedness and the lack of a unique solution of the reconstruction problem. Common L2- and L1-norm regularizations tend to produce a solution th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, we found that l 1 ‐norm regularization leads to tissue misclassification, which may be because l 1 ‐norm regularization is a linear programming problem. l p ‐norm regularization, however, can be designed to provide a quadratic cone constraint, which may give the Adam gradient descent method a more stable optimization space . The second component of the loss function is the gradient magnitude distance (GMD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we found that l 1 ‐norm regularization leads to tissue misclassification, which may be because l 1 ‐norm regularization is a linear programming problem. l p ‐norm regularization, however, can be designed to provide a quadratic cone constraint, which may give the Adam gradient descent method a more stable optimization space . The second component of the loss function is the gradient magnitude distance (GMD).…”
Section: Methodsmentioning
confidence: 99%
“…l pnorm regularization, however, can be designed to provide a quadratic cone constraint, which may give the Adam gradient descent method a more stable optimization space. 31 The second component of the loss function is the gradient magnitude distance (GMD). Between any two images, the GMD is defined as:…”
Section: D Compound Loss Functionmentioning
confidence: 99%
“…If C denotes the convex set centered with radius one with respect to · k,L 1,2 -norm then the Gaussian width of C is O( k log(d/k)) [47]. • Lp-balls (1 < p < 2) are another popular choice of constraint space [40]. The regression problem in this case is defined as:θ…”
Section: Discussion About Theorem 57mentioning
confidence: 99%
“…As an attempt to overcome the inherent technical difficulties in the ℓ 1 ‐norm approach, several authors have suggested to relax the ℓ 2 ‐ ℓ 1 regularization and to consider regularization using the penalty term Ω( x ) = ‖ x ‖ p , p ∈ (0,1), (or normalΩfalse(xfalse)=false‖xfalse‖pp), as seen in other studies. () However, the choice Ω( x ) = ‖ x ‖ p (or normalΩfalse(xfalse)=false‖xfalse‖pp) with p ∈ (0,1] or p = 2, may not ensure that all desirable properties of the regularized solution, eg, sparsity and smoothness, are captured . Taking into account these difficulties, another possibility is to consider p ∈ (1,2), ie, to deal with the ℓ 2 ‐ ℓ p Tikhonov regularized problem: xλ,p=argminxRn{}false‖bAx22+λ2false‖xpp, which, by selecting p ≈1, may be regarded as an alternative to the ℓ 1 ‐norm minimization problem that attempts to balance the effects of ℓ 1 ‐norm and the ℓ 2 ‐norm .…”
Section: Introductionmentioning
confidence: 99%